Key constitutional concepts - Imbriano, Robe.; Dellums, Erik Todd, 1964-; Zev.; Allen, Gavin; Decter, Ben.; PJ Productions; National Constitution Center (U.S.); Annenberg Foundation Trust at Sunnylands ([Philadelphia, Pa.?] : Annenberg Foundation Trust at Sunnylands, 2006)
"These three 20- minute videos examine key constitutional concepts. The first explains why the nation's framers created the Constitution. The second describes the protection of individual rights by highlighting the Supreme Court case of Gideon v. Wainwright, affirming the right to an attorney. The last explores the separation of powers by examining the Supreme Court case of Youngstown v. Sawyer, a challenge to President Truman's decision to take over steel mills during the Korean War"--Container.
part 1. Creating a constitution -- part 2. One man changes the Constitution, Gideon v. Wainwright -- part 3. Checks and balances, Youngstown v. Sawyer.
Editors, Sak Costanzo, Liz Mermin ; director of photography, Edward Marritz.
Narrator: Erik Todd Dellums ; host: Harris, Dan ; music, Gavin Allen, Ben Decter.
DVD.
Subtitled in English and Spanish.
Closed captioned for the hearing impaired.
Keywords: Gideon, Clarence Earl -- Trials, litigation, etc; Wainwright, Louie L. -- Trials, litigation, etc; Sawyer, Charles, -- b. 1887 -- Trials, litigation, etc; Truman, Harry S., -- 1884-1972.; United States; Youngstown Sheet and Tube Company -- Trials, litigation, etc; Constitutional law -- United States; Federal government -- United States; Constitutional conventions -- United States -- History; Right to counsel -- United States; War and emergency powers -- United States; Steel industry and trade -- Law and legislation -- United States; Spanish language materials -- Video recordings; United States -- Politics and government; Documentary films; DVD-Video discs; Video recordings for the hearing impaired